Pemikiran Filsafat Al-Farabi - M. Wiyono (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
Abstract: Al-Farabi was a Muslim philosopher who systematically laid the foundation of the basic Islamic philosophy in detail and easy to understand for later generations. His philosophical thoughts were influenced by the Greek philosophy. According to him, the world occurs because the first entity  (Allah) was abundant in stages called emanation. Philosophers acquired the truth by using the power of reasoning, while the prophets acquired it through God revelation to humans He chose. His thought in politics such as a major state resembles Plato's concept of ideal state. The leader is the first actor who brings citizen to happiness just like the function of the heart in a body with other organs acting as assistants to achieve the desired happiness. Abstrak: Al-Farabi adalah filososf muslim yang meletakkan dasar-dasar filsafat Islam secara sistematis dan rinci untuk memudahkan pemahaman bagi orang orang setelahnya, pemikiran filsafatnya dipengaruhi oleh pemikiran filsafat Yunani. Menurutnya alam ini terjadi dari sebab wujud pertama (Allah) yang melimpah secara bertingkat dan disebut emanasi, sedangkan untuk memperoleh kebenaran para filosof memperolehnya dengan menggunakan kekuatan akal sedangkan para Nabi memperolehnya melalui wahyu yang dituangkan kepada manusia pilihanNya. Pemikiran al-Farabi dalam bidang politik seperti negara utama menyerupai konsep negara idealnya Plato. Pemimpin adalah penggerak pertama masyarakat untuk mendapat kebahagiaan, sebagaimana kedudukan hati dalam jasad, sedangkan anggota tubuh lainnya adalah pembantu untuk menghasilkan kebahagiaan yang dicita-citakan.